Elevation of IL-17 cytokines distinguishes Kawasaki disease from other pediatric inflammatory disorders - Brodeur, Kailey E.; Liu, Meng; Ibanez, Daniel; Groot, Mareike J. de; Chen, Liang; Du, Yan; Seyal, Eman; Laza-Briviesca, Raquel; Baker, Annette; Chang, Joyce C.; Chang, Margaret H.; Day-Lewis, Megan; et al. (Arthritis & rheumatology, 2024)
Objective Kawasaki disease (KD) is a systemic vasculitis of young children that can lead to development of coronary artery aneurysms. We aimed to identify diagnostic markers to distinguish KD from other pediatric inflammatory diseases. Methods We used the proximity extension assay to profile proinflammatory mediators in plasma samples from healthy pediatric controls (n = 30), febrile controls (n = 26), and patients with KD (n = 23), multisystem inflammatory syndrome in children (MIS-C; n = 25), macrophage activation syndrome (n = 13), systemic and nonsystemic juvenile idiopathic arthritis (n = 14 and n = 10, respectively), and juvenile dermatomyositis (n = 9). We validated the key findings using serum samples from additional patients with KD (n = 37) and febrile controls (n = 28). Results High-fidelity proteomic profiling revealed distinct patterns of cytokine and chemokine expression across pediatric inflammatory diseases. Although KD and MIS-C exhibited many similarities, KD differed from MIS-C and other febrile diseases in that most patients exhibited elevation in one or more members of the interleukin-17 (IL-17) cytokine family, IL-17A, IL-17C, and IL-17F. IL-17A was particularly sensitive and specific, discriminating KD from febrile controls with an area under the receiver operator characteristic curve of 0.95 (95% confidence interval 0.89-1.00) in the derivation set and 0.91 (0.85-0.98) in the validation set. Elevation of all three IL-17-family cytokines was observed in over 50% of KD patients, including 19 of 20 with coronary artery aneurysms, but was rare in all other comparator groups. Conclusion Elevation of IL-17 family cytokines is a hallmark of KD and may help distinguish KD from its clinical mimics.